2016
DOI: 10.3386/w22041
|View full text |Cite
|
Sign up to set email alerts
|

Offshoring and Labor Markets

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 47 publications
1
66
0
Order By: Relevance
“…There is a very large literature on the effects of offshoring on labour markets which we are not able to review here, and whose conclusion vary depending on the focus (sector, period, country, data, etc.) (for surveys, see Crino, and Hummels et al ., ). Yet, if one common message emerges from this research, it is that offshoring has in many industries and countries induced important occupational changes (like job polarization), sometimes (but not always) leading to greater wage inequality.…”
Section: Research On Individual Drivers Of Inequalitymentioning
confidence: 97%
“…There is a very large literature on the effects of offshoring on labour markets which we are not able to review here, and whose conclusion vary depending on the focus (sector, period, country, data, etc.) (for surveys, see Crino, and Hummels et al ., ). Yet, if one common message emerges from this research, it is that offshoring has in many industries and countries induced important occupational changes (like job polarization), sometimes (but not always) leading to greater wage inequality.…”
Section: Research On Individual Drivers Of Inequalitymentioning
confidence: 97%
“…9 We also provide updates to the stylized facts observed for the USA. In particular, we show that the long-term decline in the employment share 4 Other papers analysing how globalization impacts the skill premium include those by Goldberg and Pavcnik (2007), Grossman and Rossi-Hansberg (2008), Acemoglu et al (2015), Burstein and Vogel (2017), and Hummels et al (2018). Iacovone et al (2013), Utar and Torres Ruiz (2013), and Mendez (2015) specifically focus on the impacts of trade on the Mexican labour market.…”
Section: Introductionmentioning
confidence: 85%
“…The many studies focusing on the evolution of offshoring, for different data and countries, and its determinants are perfectly reviewed in the recent paper of Hummels et al (2016). This literature starts with Hanson (1996, 1999) and it branches in studies analysing the offshoring determinants (that can be found in particular reviews of this literature as in Rossi-Hansberg, 2006, andDíaz andGandoy, 2007) and its evolution (Campa and Goldberg, 1997, using macroeconomic data for US, Canada, UK and Japan; and for Spain Minondo and Rubert, 2007;Díaz and Gandoy, 2005;and Gómez et al, 2006) and its effects.…”
Section: Literature Reviewmentioning
confidence: 99%